2016
DOI: 10.3989/scimar.04407.17a
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of an estuarine and a reef fish species exploited by Brazilian artisanal fishing

Abstract: Summary:In this study, we used microsatellite markers to examine the genetic structures of Centropomus undecimalis (Bloch, 1792) and Epinephelus marginatus (Lowe, 1834) populations collected from artisanal fishing sites along a stretch of coastline in southeastern Brazil. Based on F-statistics, there was no significant genetic differentiation evident in any C. undecimalis samples (F ST =0.012). However, Bayesian clustering, principal component analysis (PCA) and discriminant analysis of principal components (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Considering that the dusky grouper is an endangered species, analyzing the catches in Copacabana relative to those in previous studies on its genetics from this area is worthwhile. The population of groupers from the sites in Copacabana and Paraty, where the original catch data used to perform genetic analyses was collected, showed a significant bottleneck, with a population of 663 individuals [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the dusky grouper is an endangered species, analyzing the catches in Copacabana relative to those in previous studies on its genetics from this area is worthwhile. The population of groupers from the sites in Copacabana and Paraty, where the original catch data used to perform genetic analyses was collected, showed a significant bottleneck, with a population of 663 individuals [23].…”
Section: Discussionmentioning
confidence: 99%
“…The stock structure of most grouper species is not well understood [26]. However, data from the Priolli et al [23] study showed a bottleneck in the population of dusky groupers from the sites in Copacabana and Rio-Paraty, in southern Rio de Janeiro. Considering our results and the comparison of yearly catch data, we can conclude that there is a sustainable fishery of dusky grouper from Copacabana, Posto 6, that has the capability of maintaining a stable population of dusky groupers.…”
Section: Discussionmentioning
confidence: 99%
“…2014.Southern coastMercury contamination in this species was correlated both with site locations and body sizes. Mature larger-body indi- viduals (N 650 mm and N 8 years old) exhibited the highest mercury concentrations (harmful to humans).Condini et al (2016) Marine Pollution Bulletin Paraty and Copacabana, RJGrouper genetics Connected populations (Paraty and Ubatuba coasts)J Coast Zone Manag 2016, 19:2These values suggest that within the geographic distribution of E. marginatus from Paraty to Rio de Janeiro, there are no subdivisions of the population.The effective population size (N e ) was calculated for the only genetically differentiated group, K = 1, and resulted in 663 individuals between the Paraty (RJ) and Rio de Janeiro (RJ) populations.Priolli et al (2016) [35] ( Scientia Marina)
Fig. 1Weight-length of dusky groupers (literature, Table 2).
…”
Section: Methodsmentioning
confidence: 99%
“…Although much is known about this species in the Mediterranean, information about this species in Brazil is still scarce. Some studies on this fish have focused on investigating its biology along the southern coast of Brazil [21, 34], while others have focused on investigating its genetics [35], ecology, and fishing patterns via the evaluation of local ecological knowledge (LEK) or collaborative processes with fishers near Southeast Brazil [2, 8, 19, 36, 37]. A comprehensive review of the dusky grouper was recently published by Condini et al [21], which included an evaluation of the current knowledge of the biology and ecology of this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation